Ready to perform? A qualitative-analytic investigation into professional football goalkeepers` match warm-ups - Otte, F. W.; Millar, S. K.; Klatt, S. (International Journal of Sports Science & Coaching, 2020)
Match warm-ups in association football represent well-respected practice in order to prepare and optimise performance. While the structure of warm-ups is commonly studied from a physiological perspective, the skill and performance training approaches influencing warm-ups prior to major professional football competition appear to be particularly underexplored. Using the largely under-researched context of the football goalkeeper, the aim of this multi-method research design was to investigate two overarching research questions: (1) how are professional football goalkeeper match warm-ups structured? and (2) why does current coaching practice of expert goalkeeper coaches support this microstructure? Eleven systematic observations investigated the microstructure and training approaches applied to top-level professional football goalkeeper match warm-ups and seven semi-structured interviews with expert goalkeeper coaches further explored current coaching practice in this specific context. Results indicate that professional football goalkeeper warm-up structures include similar microstructures that progress in complexity and contain both simple `technical` and more match-representative `applied skills` exercises. Underlying reasons for goalkeeper coaches adhering to the observed warm-up structures are based on experts` understanding of applying an athlete-centred coaching approach. Hereof, goalkeeper coaches stated warm-up routines to be individualised towards goalkeeper`s needs and focused on performance stability in order to make goalkeepers feel `match-ready` and confident